"Wearing a headscarf is my personal choice" (Jasmina, 16 years) - Bartels, Edien (Islam and Christian-Muslim relations, 2005)
n March 2014, the Dutch parliament, following Denmark, passed the Combatting Forced Marriage Act in which consanguineous marriages are equated with forced marriages. Why are cousin marriages, practiced worldwide and a recognized marriage pattern in the Netherlands, high on the political agenda nowadays? We will argue that a ban on consanguineous marriages should be seen within the context of the debates and policies about migration, citizenship and transnationalism. Our argument is threefold: first, the current debate is focused on consanguineous relations among migrants and is making use of particular definitions of women’s freedom. Secondly, the different ideas about women’s freedom are the product of, and reproduce the “culturalization of citizenship.” Thirdly, the process of “othering” that occurs through the “culturalization of citizenship” in relation to consanguineous marriages, is partly based upon a politics of indignation and disgust; modes of othering that are often neglected in the analysis of culturalization discourse.